Orthopedic Traumatology An Evidence-Based Approach - Sethi, Manish K.; Jahangir, A. Alex.; Obremskey, William T.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Evidence-based medicine is the future of orthopedic surgery. The escalating costs of medical care drive the need for physicians to base clinical decisions on data in order to provide optimal care to every patient.  Orthopedic Traumatology: An Evidence-Based Approach provides readers a model for evidence-based decision making in orthopedic trauma.  Renowned orthopedic trauma surgeons describe interesting clinical scenarios, give expert opinions on management, and include relevant imaging to create a complete picture of each fascinating case.  Useful for residents and practicing physicians alike, Orthopedic Traumatology is a unique guide to orthopedic trauma and evidence-based medicine.
Part 1: Evidence Based Medicine in Orthopedic Trauma Surgery -- Introduction to Evidence Based Medicine -- Part 2: Spine Trauma -- Cervical Spine Clearance -- Cervical Spine Fracture Dislocation -- Lumbar Burst Fractures -- Part 3: Upper Extremity Trauma -- Scapula Fractures -- Clavicle Fractures -- Proximal Humerus Fractures -- Humeral Shaft Fractures -- Distal Humerus Fractures -- Distal Radius Fractures -- Part 4: Acetabular, Hip and Pelvic Trauma -- Acetabular Fractures in the Elderly -- Pelvic Ring Injury I -- Pelvic Ring Injury II -- Femoral Neck Fractures in the Elderly -- Intertrochanteric Femur Fractures -- Part 5: Lower Extremity Trauma -- Diaphyseal Femur Fractures -- Distal Femur Fractures -- Knee Dislocations -- Tibial Plateau Fractures -- Closed Diaphysial Tibia Fractures -- Open Diaphyseal Tibia Fractures -- Part 6: Foot and Ankle Trauma -- Pilon Fractures -- Ankle Fractures -- Calcaneus Fractures -- Talus Fractures -- Part 7: Polytrauma, Infection and Perioperative Management of the Orthopedic Trauma Patient -- Damage Control -- DVT Prophylaxisin Orthopedic Trauma -- The Infected Tibial Nail -- Perioperative Optimization in Orthopedic Trauma.
Keywords: Orthopedics; Orthopedics; Surgical Orthopedics